A Biomass‐Based Integral Approach Enables Li‐S Full Pouch Cells with Exceptional Power Density and Energy Density. Issue 14 (24th May 2021) - Liu, Yuping; Barnscheidt, Yvo; Peng, Manhua; Bettels, Frederik; Li, Taoran; He, Tao; Ding, Fei; Zhang, Lin
Abstract: Lithium‐sulfur (Li‐S) batteries, as part of the post‐lithium‐ion batteries (post‐LIBs), are expected to deliver significantly higher energy densities. Their power densities, however, are today considerably worse than that of the LIBs, limiting the Li‐S batteries to very few specific applications that need low power and long working time. With the rapid development of single cell components (cathode, anode, or electrolyte) in the last few years, it is expected that an integrated approach can maximize the power density without compromising the energy density in a Li‐S full cell. Here, this goal is achieved by using a novel biomass porous carbon matrix (PCM) in the anode, as well as N‐Co9 S8 nanoparticles and carbon nanotubes (CNTs) in the cathode. The authors' approach unlocks the potential of the electrodes and enables the Li‐S full pouch cells with unprecedented power densities and energy densities (325 Wh kg −1 and 1412 W kg −1, respectively). This work addresses the problem of low power densities in the current Li‐S technology, thus making the Li‐S batteries a strong candidate in more application scenarios. Abstract : The Li‐S full pouch cells with unprecedented power densities and energy densities are achieved using a biomass‐enabled integral approach: a novel biomass porous carbon matrix in the anode, as well as N‐Co9 S8 nanoparticles and carbon nanotubes in the cathode, unlocks the potential of the electrodes, thus making the Li‐S batteries a strong candidate in more application scenarios. ​